ASCOT study: consequences and lessons - S. A. Boytsov (Кардиоваскулярная терапия и профилактика)
ASCOT study results influenced the content of the British National guidelines on arterial hypertension (AH) 2006 and the European Hypertension Society guidelines 2007. This study demonstrated that AH treatment with “new” antihypertensives (calcium antagonists, ACE inhibitors) is more effective and more metabolically safe than treatment with “old” agents (diuretics, beta-adrenoblockers). It has been shown that vessel organo-protection includes not only delaying atherosclerosis progression, but also decreasing arterial stiffness. Reducing blood pressure (BP) in aorta is more important than brachial BP decrease; arterial stiffness reduction is one of the crucial characteristics of antihypertensive medications. Despite lower effectiveness of beta-adrenoblockers in AH complication prevention, these agents still remain among main antihypertensive classes.